Are Bentong ginger (Zingiber officinale) biosynthesized silver nanoparticles safe and effective? An optimization, characterization, and toxicity evaluation study - Abd Jabar, Nor Azmiraah; Nor-Khaizura, Mahmud Ab Rashid; Ismail, Siti Izera; Loo, Yuet Ying; Chong, Kah Hui; Padmanabhan, Kousalya; Jiang, Shan (Elsevier, 2024)
The biosynthesis of silver nanoparticles from ginger extract is particularly interesting due to the bioactive compounds present in ginger, which have antioxidant, antimicrobial, and anti-inflammatory properties. The study aims to optimize, characterize, and evaluate the toxicity value of the biosynthesized silver nanoparticles using Bentong ginger (Zingiber officinale) rhizome extract and commercialized ginger powder extract as reducing and capping agents. The synthesis was optimized regarding pH, silver nitrate concentration, and incubation time for better yield and stability. Additionally, biosynthesized silver nanoparticles were characterized using UV–vis spectrophotometer, X-ray diffraction, Fourier-transform Infrared, and Transmission Electron Microscope analysis. Cytotoxicity test was done using brine shrimp lethality test to determine toxicity value. The result for both Bentong ginger rhizome extract and commercialized ginger powder extract indicated that the maximum absorption of biosynthesized silver nanoparticles was 450 nm, with the most optimum pH of 11, 1 mM of silver nitrate concentration, and incubation time of 24 h. The nanoparticles were almost spherical, with an average particle size of 15.08 ± 6 nm. The analysis confirms the presence of phytochemicals in the ginger extract that aids in reducing silver ions into silver nanoparticles. Brine shrimp lethality assay showed the LC50 for AgNPs was medium toxic at 838.31 µg/mL. Although silver nanoparticles possess antimicrobial ability, the potential toxicity to human health and environmental concerns must be considered before deploying into food industries. This is the first report utilizing Bentong ginger in silver nanoparticle synthesis.